Establishment of a new peritrich ciliate genus, Pseudepistylis n. gen. (Ciliophora: Peritrichia: Epistylididae), with a description of a new freshwater species, Pseudepistylis songi n. sp. from Wenzhou, China - Peng, Xiaohui; Shi, Xinlu; Warren, Alan (Zootaxa, 2007)
A new colonial sessilid peritrich genus, Pseudepistylis, is established. Pseudepistylis n. gen. belongs to the family Epistylididae, (i.e. colonial with a non-contractile stalk and peristomial disc not borne on a stalk) but has oral ciliature that makes less than two turns on the peristome before entering the infundibulum and a reticulate silverline system. Morphology, infraciliature and silverline system of the type species Pseudepistylis songi n. sp., isolated from a freshwater pond near Wenzhou, China, have been investigated both in vivo and following silver impregnation. The new species is characterized by small colony size of only one to eight zooids borne upon a slender, dichotomously branched stalk. Zooids are bell-shaped, in vivo approximately 220 × 140 μ m, with wide peristomial lip that are invariably reflected aborally, single contractile vacuole at the dorsal wall of the infundibulum, and C-shaped macronucleus. The pellicle of contracted zooids shows several large, characteristic folds. The silverline system is reticulate with at least 137 silverlines between the peristomial area and the aboral ciliary wreath and approximately 77 between the aboral ciliary wreath and the scopula. The haplokinety and polykinety complete approximately one and one-quarter turns of the peristome before entering the infundibulum. Within the infundibulum the kineties of infundibular polykinety 2 (P2) terminate at different levels between P1 and P3. The myoneme system is also described.